Roles of Eco-labeling in Fisheries Conservation and Sustainability - Olaniyi Alaba Olopade; Henry E. Dienye (Marine Science Department Diponegoro University, 2017)
An important goal of fisheries management is to ensure that fish stocks are harvested at sustainable levels of fishing pressure. However, the classical maximum sustainable yield theory and its derivatives have not worked for fisheries management. A number of mitigating measures have been suggested of which eco -labeling is one. An ecolabel on a fish product is a distinctive mark or statement indicating that it has been harvested in compliance with preset sustainability standards. This paper examines eco labeling in fisheries as the new strategy to achieve fisheries conservation and sustainability. It emphasizes the importance of fish as critical food resources and new approach to fisheries management through the use of certification programs. It considers the benefits and problems that may accrue from eco-certification of fish harvesting and trade practices in fisheries. This paper, attention is focused on examining the likely option for development of eco-labeling scheme in Nigeria. The paper concludes that the increase awareness amongst stakeholders of the potential role of eco-labeling in conservation and sustainability tools should be established. Keywords: Fisheries management, fish, conservation, eco-certification